Investigation of Circular Construction Waste Management (CCWM) Practices in Malaysia - Devendra Subramaniam; Sasitharan Nagapan (Journal of Structural Monitoring and Built Environment, 2025)
This research investigates the adoption of Circular Construction Waste Management (CCWM) practices in Malaysia, focusing on the environmental and economic challenges posed by construction waste. The study aims to identify key challenges, determine effective waste management practices, and propose sustainable solutions to enhance resource efficiency. A quantitative survey was conducted with data analyzed using SPSS for reliability and descriptive insights involving 130 construction personnel such as those engineers, project managers, main contractors, construction manager, site consisting of workers, and supervisors. The findings reveal that the high cost of recycled materials mean value 4.85 are the most critical barriers to adopting circular economy principles. Among the recommended practices, the "3R" approach Reduce, Reuse, Recycle emerged as the highly effective practice with the highest mean value of 4.89. By adopting these practices, stakeholders can reduce environmental impacts, improve resource efficiency, and achieve a more sustainable construction industry.